Respuesta :
An algebraic equation enables the expression of equality between variable expressions
[tex]\underline{The \ value \ of \ [AEF] \ is \ \dfrac{4}{9}}[/tex]
The reason the above value is correct is given as follows:
The given parameters are;
The symbol for the area of a triangle ΔXYZ = [XYZ]
The side length of the given square ABCD = 1
The location of point E = Side [tex]\overline{BC}[/tex] on square ABCD
The location of point F = Side [tex]\overline{CD}[/tex] on square ABCD
∠EAF = 45°
The area of ΔCEF, [CEF] = 1/9 (corrected by using a similar online question)
Required:
To find the value of [AEF]
Solution:
The area of a triangle = (1/2) × Base length × Height
Let x = EC, represent the base length of ΔCEF, and let y = CF represent the height of triangle ΔCEF
We get;
The area of a triangle ΔCEF, [CEF] = (1/2)·x·y = x·y/2
The area of ΔCEF, [CEF] = 1/9 (given)
∴ x·y/2 = 1/9
ΔABE:
[tex]\overline{BE}[/tex] = BC - EC = 1 - x
The area of ΔABE, [ABE] = (1/2)×AB ×BE
AB = 1 = The length of the side of the square
The area of ΔABE, [ABE] = (1/2)× 1 × (1 - x) = (1 - x)/2
ΔADF:
[tex]\overline{DF}[/tex] = CD - CF = 1 - y
The area of ΔADF, [ADF] = (1/2)×AD ×DF
AD = 1 = The length of the side of the square
The area of ΔADF, [ADF] = (1/2)× 1 × (1 - y) = (1 - y)/2
The area of ΔAEF, [AEF] = [ABCD] - [ADF] - [ABE] - [CEF]
[ABCD] = Area of the square = 1 × 1
[tex][AEF] = 1 - \dfrac{1 - x}{2} - \dfrac{1 - y}{2} - \dfrac{1}{19}= \dfrac{19 \cdot x + 19 \cdot y - 2}{38}[/tex]
From [tex]\dfrac{x \cdot y}{2} = \dfrac{1}{9}[/tex], we have;
[tex]x = \dfrac{2}{9 \cdot y}[/tex], which gives;
[tex][AEF] = \dfrac{9 \cdot x + 9 \cdot y - 2}{18}[/tex]
Area of a triangle = (1/2) × The product of the length of two sides × sin(included angle between the sides)
∴ [AEF] = (1/2) × [tex]\overline{AE}[/tex] × [tex]\overline{FA}[/tex] × sin(∠EAF)
[tex]\overline{AE}[/tex] = √((1 - x)² + 1), [tex]\overline{FA}[/tex] = √((1 - y)² + 1)
[AEF] = (1/2) × √((1 - x)² + 1) × √((1 - y)² + 1) × sin(45°)
Which by using a graphing calculator, gives;
[tex]\dfrac{1}{2} \times \sqrt{(1 - x)^2 + 1} \times \sqrt{(1 - y)^2 + 1} \times \dfrac{\sqrt{2} }{2} = \dfrac{9 \cdot x + 9 \cdot y - 2}{18}[/tex]
Squaring both sides and plugging in [tex]x = \dfrac{2}{9 \cdot y}[/tex], gives;
[tex]\dfrac{(81 \cdot y^4-180 \cdot y^3 + 200 \cdot y^2 - 40\cdot y +4)\cdot y^2}{324\cdot y^4} = \dfrac{(81\cdot y^4-36\cdot y^3 + 40\cdot y^2 - 8\cdot y +4)\cdot y^2}{324\cdot y^2}[/tex]
Subtracting the right hand side from the equation from the left hand side gives;
[tex]\dfrac{40\cdot y- 36\cdot y^2 + 8}{81\cdot y} = 0[/tex]
36·y² - 40·y + 8 = 0
[tex]y = \dfrac{40 \pm \sqrt{(-40)^2-4 \times 36\times 8} }{2 \times 36} = \dfrac{5 \pm \sqrt{7} }{9}[/tex]
[tex][AEF] = \dfrac{9 \cdot x + 9 \cdot y - 2}{18} = \dfrac{9 \cdot y^2-2 \cdot y + 2}{18 \cdot y}[/tex]
Plugging in [tex]y = \dfrac{5 + \sqrt{7} }{9}[/tex] and rationalizing surds gives;
[tex][AEF] = \dfrac{9 \cdot \left(\dfrac{5 + \sqrt{7} }{9}\right) ^2-2 \cdot \left(\dfrac{5 + \sqrt{7} }{9}\right) + 2}{18 \cdot \left(\dfrac{5 + \sqrt{7} }{9}\right) } = \dfrac{\dfrac{40+8\cdot \sqrt{7} }{9} }{10+2\cdot \sqrt{7} } = \dfrac{32}{72} = \dfrac{4}{9}[/tex]
Therefore;
[tex]\underline{[AEF]= \dfrac{4}{9}}[/tex]
Learn more about the use of algebraic equations here:
https://brainly.com/question/13345893
![Ver imagen oeerivona](https://us-static.z-dn.net/files/dd3/9e6d1a7f0244f3aa4fb7afc500c3e06e.jpg)